A conserved role for the ARC1 E3 ligase in Brassicaceae self-incompatibility - Indriolo, Emily; Goring, Daphne R. (Frontiers in Plant Science, 2014)
Ubiquitination plays essential roles in the regulation of many processes in plants including pollen rejection in self-incompatible species. In the Brassicaceae (mustard family), self-incompatibility drives the rejection of self-pollen by preventing pollen hydration following pollen contact with the stigmatic surface. Self-pollen is recognized by a ligand-receptor pair: the pollen S-locus Cysteine Rich/S-locus Protein 11 (SCR/SP11) ligand and the pistil S Receptor Kinase (SRK). Following self-pollen contact, the SCR/SP11 ligand on the pollen surface binds to SRK on the pistil surface, and the SRK-activated signaling pathway is initiated. This pathway includes the ARM Repeat Containing 1 (ARC1) protein, a member of the Plant U-box (PUB) family of E3 ubiquitin ligases. ARC1 is a functional E3 ligase and is required downstream of SRK for the self-incompatibility response. This mini review highlights our recent progress in establishing ARC1’s conserved role in self-pollen rejection in Brassica and Arabidopsis species and discusses future research directions in this field.